Explorar se mudanças em desfechos psicossociais, induzidas pela educação em neurociência da dor, podem ser transferidas para desfechos funcionais no contexto da dor lombar crônica: ensaio clínico aleatorizado - Suguiura, Iully Tiyoko Rebelatto (2024)
Introduction: Psychosocial factors have a negative impact on chronic low back pain (CLBP), but it is unclear whether subgroups stratified by risk of poor prognosis show differences in clinical-functional outcomes. Furthermore, it is known that pain neurophysiology education (PNE) is an effective therapeutic strategy for improving psychosocial outcomes in chronic pain. However, there is a scarcity of studies investigating whether these improvements in psychosocial aspects resulting from PNE translate into improvements in functional outcomes. Objective: The general objective of this study was to identify clinical-functional differences and assess the short-term repercussions of a PNE program between different risk strata of poor prognosis on the psychosocial, neuromuscular and locomotor aspects of volunteers with CLBP. Methods: The first study was a cross-sectional observational study and the second a randomized clinical trial. The sample of the first study was made up of 89 volunteers, and the second of 72. All the volunteers had CLBP and were aged between 18 and 59, who were stratified according to the risk of poor prognosis for pain. The analyses took place between November 2022 and December 2023. Results: In the first study, a statistically significant risk score effect was observed for almost all outcomes, except for the ratio between isometric strength and strength endurance. For psychosocial outcomes, there was a tendency for scores to increase the higher the risk. In the neuromuscular and locomotor outcomes, there was a tendency for performance to decrease the higher the risk. In the second study, the risk of poor prognosis affected the outcomes in such a way that the higher the risk, the greater the repercussions; the type of intervention (NDT or control) had no effect on the outcomes; the time of assessment (pre- or post-intervention) had positive repercussions at the post-intervention time. Conclusion: It is concluded that the degree of risk of poor prognosis induces statistical differences between clinical-functional outcomes in people with CLD. The educational interventions showed positive repercussions, regardless of the quality of the information provided, pointing to a transfer of psychosocial gain to clinical-functional outcomes.